Rivalry of celebrity and influencer endorsement for advertising effectiveness - Pramesthi, Hanum Kanthi; Prasetyo, Bambang Dwi; Safitri, Reza (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
Using the theoretical framework of the elaboration likelihood model, this study attempts to analyze the level of difference in effectiveness between celebrity and influencer endorsement in social media advertising to influence consumer purchase intention. This study highlights the phenomenon of Pantene Indonesia's social media advertising, which is endorsed by Maudy Ayunda as a celebrity endorsement and Keanu Angelo as an influencer endorsement, by comparing these two categories of endorsers. This study uses a positivist paradigm, a quantitative approach, and a survey to collect data. Questionnaires were distributed online to 400 respondents for a month in December 2023. The study used a non-parametric test because the data did not meet the normality assumption. Comparative hypotheses were tested using the Wilcoxon Signed Rank Test with the assistance of SPSS 25. The study results indicate a significant difference between the use of influencer and celebrity endorsements in social media advertising to drive consumer purchase intention. This is demonstrated through the significance values of all variables: the quality of arguments (X1), source credibility (X2), attractiveness (X3), and purchase intention (Y), which are less than 0.005. Furthermore, the study reveals that celebrity endorsements have a higher effectiveness level than influencer endorsements. The comparative mean scores for all variables show that the average for celebrity endorsement is 37.85 compared to influencer endorsement at 36.29, which is proof of this. Through the most important route of the elaboration likelihood model that is, the quality of the endorser's arguments—consumers evaluate social media advertising messages, resulting in more persistent increases in attitudes such purchase intention.